Influence mechanism of epoxy resin and curing agent on high-temperature performance of asphalt - Gao, Mingxing; Xue, Yanhua; Guan, Peng; Yuan, Feilong (Penerbit Universiti Kebangsaan Malaysia, 2020)
To deeply show the internal reasons for the effects of epoxy resin and curing agent on the high-temperature performance of asphalt, nine kinds of asphalt with different content of epoxy resin and curing agent were prepared. On the premise of ensuring that the softening point, penetration and ductility of epoxy asphalt no attenuation, the dynamic shear rheology test and Saybolt viscosity test were used to examine the rutting factor (G*/sin δ), complex shear modulus (G*), phase angle (δ), and viscosity of asphalt with different epoxy resin and curing agent contents. With the help of fluorescence microscopy, microscopic morphology was analyzed, and the micro-image was further analyzed quantitatively by using 3Dsurface and particle statistics. The results show that adding epoxy resin and curing agent into asphalt can significantly improve the rutting factor and complex shear modulus of asphalt and reduce the phase angle and the viscosity growth rate of asphalt changed from fast to slow. Fluorescence and 3Dsurface imaging results indicate when the epoxy resin and the curing agent are uniformly distributed and forms microflocculent structures, the epoxy resin can fully swell in asphalt, and the fluorescence intensity is uniform. The statistical analysis of particles shows that the improvement in high-temperature performance of asphalt by epoxy resin and curing agent results from the distribution of particle area above 26.7346 μm2. The high-temperature performance of epoxy asphalt is optimal when the content of epoxy resin and curing agent is 6 %.